Ideology, Social Commentary and Resistance in Popular Music: A Case Study of Singapore - Chye, Phua Siew (Institutional Knowledge at Singapore Management University, 1996)
Popular music as a site of struggles over meaning is focused upon, where the social and political relations between different groups in Singapore society are mirrored. How ruling elites and everyday people make use of the same cultural form--popular music--for different purposes is examined.